Pengaruh Kualitas Informasi Instagram Lembaga BAZNAS RI (@baznasindonesia) Terhadap Pengamalan Zakat, Infak, Sedekah (ZIS) Followers - Amrullah, Gilang Musfi; Nuryudi, Nuryudi (Librarianship in Muslim Societies, 2023)
The Instagram account @baznasindonesia is the main source for the public in finding information and references regarding activities related to zakat. The purpose of this study was to measure how well followers evaluate the quality of information on Instagram @baznasindonesia, to measure how much Zakat, Infak, Sedekah (ZIS) practices are practiced by followers on the Instagram @baznasindonesia account, and to measure how much influence the quality of information has on the practice of Zakat, Infak, Sedekah (ZIS) instagram followers @baznasindonesia. The research method in this study is quantitative with simple linear regression as the data analysis technique. The sample used was 100 respondents taken from followers of the @baznasindonesia Instagram account with a questionnaire. The results showed that the quality of information was considered very good with a total mean of 3.40 in the scale range of 3.25 – 4.00 (Very High) and the practice of Zakat, Infaq, Sedekah (ZIS) had a total mean of 2.93 in the scale range of 2. .50 – 3.24 (High). Furthermore, the quality of information has a fairly strong correlation with the practice of ZIS, which is equal to 0.483 which is in the range > 0.25 – 5 (quite strong), and the amount of influence given by the quality of information on the practice of Zakat, Infaq, Sedekah (ZIS) is 0.233 or 23 ,3 %. Based on the results of the study, instagram @baznasindonesia managers from BAZNAS RI need to add more comprehensive information, such as integrating information owned by BAZNAS RI on Instagram @baznasindonesia .